5-Hydroxytryptamine receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database - Andrade, Rodrigo; Barnes, Nicholas M.; Baxter, Gordon; Bockaert, Joel; Branchek, Theresa; Butler, Amy; Cohen, Marlene L.; Dumuis, Aline; Eglen, Richard M.; Göthert, Manfred; Hamblin, Mark; Hamon, Michel; et al. (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
5-HT receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on 5-HT receptors [194] and subsequently revised [176]) are, with the exception of the ionotropic 5-HT3 class, GPCRs where the endogenous agonist is 5-hydroxytryptamine. The diversity of metabotropic 5-HT receptors is increased by alternative splicing that produces isoforms of the 5-HT2A (non-functional), 5-HT2C (non-functional), 5-HT4, 5-HT6 (non-functional) and 5-HT7 receptors. Unique amongst the GPCRs, RNA editing produces 5-HT2C receptor isoforms that differ in function, such as efficiency and specificity of coupling to Gq/11 and also pharmacology [40, 482]. Most 5-HT receptors (except 5-ht1e and 5-ht5b) play specific roles mediating functional responses in different tissues (reviewed by [463, 382]).